The Effectiveness Of The Use Of Decision-Making Tools And WHO Wheel Criteria In the Selection Of Contraception For Post Partum Mother - Iva Gamar Dian Pratiwi; Nailiy Huzaimah; Ratna Indriyani (Chakra Brahmanda Lentera Institute, 2022)
Background: According to the World Health Organization (WHO), family planning is a program with several objectives, including regulating the number of children, regulating births between children, and anticipating unwanted pregnancies. According to data from the Central Statistics Agency for 2019, the number of contraceptive uses of all types in East Java was 66.24 percent, lower than in 2018, 67.88 percent. The number of contraceptive methods used at BPM Kiswaniyah for postpartum women in 2021 is higher than Long-Term Contraceptive Methods, which is 90 percent, compared to the MKJP method, which is only 10 percent. This study aimed to determine differences in the effectiveness of using the WHO Wheel Criteria and Decision-Making Assistance Tool (ABPK) in the selection of contraception by postpartum mothers.Methods: This research is a type of pre-experimental research, using a post-test-only control group design approach to determine differences in the effectiveness of using the WHO Wheel Criteria and Tools. The location of this study was at BPM Kiswaniyah during the time of the research from July to September 2022. The population in this study were all postpartum mothers (0-40 days), totaling 40 people. The independent sample t-test formula is used when the normality and normal distribution of data is tested to find the difference in the mean value between one group and another. Results: Data analysis A significance value of 0.002<0.05was obtained, which can be concluded that there is no significant difference between the effectiveness of using ABPK and WHO Wheel Criteria in the selection of postpartum Conclusion: contraception.ABPK and WHO Wheel Criteria have the same effectiveness in helping clients when choosing contraception after giving birth. This is possible due to several reasons, including the insufficient number of samples, the ability of each midwife to use contraceptive selection tools and the different understanding of respondents.